THOUGHT IN THE SERVICE OF INTUITION: HEIDEGGER’S APPROPRIATION OF KANT’S SYNTHETIC A PRIORI IN DIE FRAGE NACH DEM DING (Revista Kriterion, 2020)
There is general agreement that Kant’s thought strongly influenced Heidegger’s. Nevertheless, there is still much work to be done in order to fully appreciate this influence. A central theme to disclose the relation between these authors is the role they give to the transcendental. In this paper I show that Kant’s account of intuition is the focus of Heidegger’s interpretation of Kant in his Die Frage nach dem Ding, since Heidegger interprets Kant’s treatment of intuition as a delimiting of the modern mathematical tendency to determine everything out of pure reason alone. I argue that this interpretation is at the basis of Heidegger’s appropriation of Kant’s synthetic a priori in this work, the aim of which is to take this notion away from the sphere of the objects of mathematical physical science, and place it in the realm of everyday experience. I claim that Heidegger thinks that this move can only be accomplished by removing universality and necessity (epistemic certainty) from Kant’s a priori. Finally, I show that Heidegger’s appropriation of Kant’s synthetic a priori goes together with and illuminates his understanding of transcendence as das Zwischen, ‘the between us and things’.